Approach to Choosing Communication Strategies of Social Projects Based on Indistinct Liguistic Method - Ju. V. Loginova; I. V. Loginov (Вестник Российского экономического университета имени Г. В. Плеханова)
Communication strategies of promoting goods, services and brands form an integral part of marketing strategies. Resolving the problem of choosing communication strategy is based on expert opinion of one or several specialists, whose position can be taken by professionals in promotion of commercial and social goods. The goal is to choose the best alternative of conducting communication campaigns based on its potential effectiveness. The article uses mathematic tools of fluctuating set of indistinct linguistic terms in order to resolve the problem of choosing communication strategy for social projects. On this basis the task was formulated for decision-making concerning the choice of marketing strategy in conditions of uncertainty and an example was provided for choosing communication strategy of promoting a social project. As an example of using these tools the inter-regional literature camping ‘War and Peace’ was studied, where a multitude of 3 alternatives was formed, expert opinions in the form of linguistic expressions were obtained and the multitude of alternatives was regulated on the basis of non-dominant strategy. Findings of the research show possibility to use indistinct linguistic computing model for decision-making in marketing.